The Identification of Open Space Area Sport in Universitas Negeri Semarang - Setiawan, Ipang; Purwono, Endro Puji; Yuwono, Cahyo; Dharmawan, Dhimas Bagus (Department of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this research is to identify and review about open space sport owned by the Unnes support the conservation of the physical quality of the civitas academica. In this study the method used is descriptive survey method with a quantitative approach in terms of Sport Development Index (SDI). The source of this research data obtained from the sample and research the informant, the technique used is the Puposive and Snowball Sampling and research instrument used is the interview, observation and data analysis used in this research is quantitative approach with the use of SDI analysis dimension of open space. The results of this research data is a number of open spaces sports that are on the Unnes is 24 temples with a total area of 31,161.72 m2, while the total population of civitas academica totaled 37,700 souls, next in the index could open space sport in Unnes is 0.236. The index values can be summed up open space obtained shows that if in the review of the norms of SDI (Sport Development Index) the availability of open space at Unnes is still in the low category.